Ideas in Marketing: Finding the New and Polishing the Old Proceedings of the 2013 Academy of Marketing Science (AMS) Annual Conference - Kubacki, Krzysztof; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
Founded in 1971, the Academy of Marketing Science is an international organization dedicated to promoting timely explorations of phenomena related to the science of marketing in theory, research, and practice. Among its services to members and the community at large, the Academy offers conferences, congresses and symposia that attract delegates from around the world. Presentations from these events are published in this Proceedings series, which offers a comprehensive archive of volumes reflecting the evolution of the field. Volumes deliver cutting-edge research and insights, complimenting the Academy’s flagship journals, the Journal of the Academy of Marketing Science (JAMS) and AMS Review. Volumes are edited by leading scholars and practitioners across a wide range of subject areas in marketing science.  This volume includes the full proceedings from the 2013 Academy of Marketing Science (AMS) Annual Conference held in Monterey, California, entitled Ideas in Marketing: Finding the New and Polishing the Old.
Customer Satisfaction and Loyalty in the Service Sector -- Sales Process and Performance -- Social Media Branding & Human Brands -- Social Consumption and the Self -- Understanding Pricing & Consumer Behavior -- Customer Behaviour in Retail Settings -- Sustainable Marketing -- Changing Brand Perceptions -- Social Marketing: Corporate and Strategic Perspectives -- Political Marketing Theory: Targeting the Consumer Voter -- Consumer Behavior Trends from a Latin American Perspective -- Ahoy There! Ensuring Successful Relationships -- Green Consumer Behavior -- Doctoral Colloquium Session 4: Strategic Issues -- Market Orientation, Product Innovation, and Performance -- B2B Relationship Capabilities Value and Benefits -- Customer Satisfaction and Customer Service -- Advances in Mobile Marketing and Its Many Tentacles -- Theories of Attitude, Memory, Love -- Technology Application and Analyses in Retailing -- Crowd Marketing for the Marketing Crowd -- Doctoral Colloquium Session I: Research Methods and Measurement -- Targeting the New Consumer -- Social Marketing and Social Communication -- Entrepreneurship: Orientation, Planning, and Performance -- Political Marketing: Lessons from North American Campaigning -- Marketing Communication in Social Media -- Consumption and Health -- Sex, Drugs, and Humor...Themes in Advertising -- Lamb-Hair-McDaniel AMS Outstanding Marketing Teacher Award -- Contemporary Issues in Wine Marketing -- A Potpourri of Brick and Click Issues -- New Insights into Students Learning in Groups -- The Critical Role of Marketing in Supply Chain Management -- Advertising: Theory and Environment -- Links Between Brands -- In Search of Gratification -- Sport Sponsorship -- Country Image and International Segmentation -- Intangible Factors Affecting Brands -- Doctoral Colloquium Session 2: Consumer Behavior Issues -- Channel Structures, Relationships and Contexts -- Factors Affecting Good and Bad Relationships in the Marketplace -- Retail Staff Interaction and Outcomes -- Online Advertising and WOM -- Advances in Sustainable Supply Chain Management -- International Marketing Strategy -- Doctoral Colloquium Session 3: B2B Issues -- Advertising: Measurement and Sponsorship Issues -- International Marketing Expansion -- Marketing Research and Methods -- Political Marketing: Cases, Culture, and Policy -- Pricing Implications for Promotion Strategy -- Managing Product Information Online -- Ethical Marketing Issues -- Sustainability and Consumers -- Emerging Concepts in Service Engagement -- Social Media Affinity and Empowerment -- Emotions, Associations, and Other Brand Influences -- Strategies, Preferences and Pestering -- International Customer Behavior -- Sensory Marketing Through Scent, Taste, and Neuroscience -- Doctoral Colloquium Session 5: Sex, Social Media, and Identity-Signaling -- Technology and Sales -- A Town Hall Meeting with Editorial Reviewers -- Value Creation and The Role of Community in Customer Interactions -- Innovation in Wine and Marketing Research -- Emerging Markets: Why African Markets Offer More Than You Think! -- Social Responsibility in Marketing Education -- The Influence of Brands -- Who Needs a Sales Manager? -- Art and Emotion -- Knowledge is Power -- Till Some New Player Us Do Part -- International Marketing Communications -- Sensory Marketing in the Digital Age -- To Possess or Not to Possess -- European Perspectives on Marketing -- Social Media and Trust, Diffusion, and User Experience -- Wanting that Object -- Emerging Thoughts in Social Media -- Sensory Marketing Through Touch -- To Adopt or Not to Adopt New Market and Technological Offerings.
Keywords: Marketing; Leadership; Sales management; Marketing; Business Strategy/Leadership.; Sales/Distribution.